PENGARUH TINGKAT PENDIDIKAN, INDEKS PEMBANGUNAN GENDER (IPG) DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA PEREMPUAN DI PROVINSI JAMBI - Tri Suciana Situmorang; Rosmeli Rosmeli; Dwi Hastuti (Jurnal Daya Saing, 2026)
This research, entitled "The Effect of Education Level, Gender Development Index (GDI), and Economic Growth on the Female Labor Force Participation Rate in Jambi Province," aims to analyze the development of education level, Gender Development Index (GDI), economic growth, and the Female Labor Force Participation Rate (TPAKP), as well as the influence of education level, GDI, and economic growth on the TPAKP in Jambi Province. This study uses secondary data in the form of panel data consisting of 11 districts/cities in Jambi Province during the 2020–2024 period. The analytical method used is panel data regression with a Fixed Effects Model (FEM) approach. The results of the study indicate that the development of the Female Labor Force Participation Rate (TPAKP), education level, Gender Development Index (IPG), and economic growth in Jambi Province during the study period tended to fluctuate. Based on the results of panel data regression estimation, the education level variable has a negative and significant effect on TPAKP. The IPG variable has a positive and significant effect on TPAKP. Meanwhile, the economic growth variable has no significant effect on TPAKP. Simultaneously, education level, IPG, and economic growth have a significant effect on TPAKP in Jambi Province